2014
DOI: 10.1186/1471-2369-15-114
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of progression to chronic dialysis in survivors of severe acute kidney injury: a competing risk study

Abstract: BackgroundSurvivors of acute kidney injury are at an increased risk of developing irreversible deterioration in kidney function and in some cases, the need for chronic dialysis. We aimed to determine predictors of chronic dialysis and death among survivors of dialysis-requiring acute kidney injury.MethodsWe used linked administrative databases in Ontario, Canada, to identify patients who were discharged from hospital after an episode of acute kidney injury requiring dialysis and remained free of further dialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 37 publications
(54 reference statements)
10
38
0
1
Order By: Relevance
“…Our analysis suggests that BMI, baseline eGFR, low MAP, low prealbumin level, hypoalbuminemia, oliguria, BUN level, and more severe AKI stage were independent risk factors associated with death or renal nonrecovery. Other studies have identified advanced age, preexisting diabetes mellitus, decreased baseline eGFR,27 higher Charlson comorbidity index score,28 or hypomagnesemia23 as risk factors for renal nonrecovery in AKI survivors. Following a community-based study of patients older than 65 years, Sesso et al found a relationship between the rate of decline in eGFR with age and baseline eGFR, a result similar to that observed by Collins et al29,30 In contrast, Schiffl did not find any prognostic indicators related to partial recovery (defined as SCr >115 µmol/L at hospital discharge) when analyzing 226 critically ill patients with previous normal RF who had AKI requiring dialysis 25.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis suggests that BMI, baseline eGFR, low MAP, low prealbumin level, hypoalbuminemia, oliguria, BUN level, and more severe AKI stage were independent risk factors associated with death or renal nonrecovery. Other studies have identified advanced age, preexisting diabetes mellitus, decreased baseline eGFR,27 higher Charlson comorbidity index score,28 or hypomagnesemia23 as risk factors for renal nonrecovery in AKI survivors. Following a community-based study of patients older than 65 years, Sesso et al found a relationship between the rate of decline in eGFR with age and baseline eGFR, a result similar to that observed by Collins et al29,30 In contrast, Schiffl did not find any prognostic indicators related to partial recovery (defined as SCr >115 µmol/L at hospital discharge) when analyzing 226 critically ill patients with previous normal RF who had AKI requiring dialysis 25.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, data from large cohorts suggest that approximately one of every 12 survivors of AKI-D who become dialysis independent will require long-term dialysis within 3-5 years (39,40). Increased risk of ESRD occurs regardless of baseline CKD status.…”
Section: Long-term Outcomes Of Patients With Aki-d Who Become Dialysimentioning
confidence: 98%
“…The risk of ESRD after AKI-D after early dialysis independence is substantial, ranging from 8% to 21% of survivors (12,39). A large cohort of 4383 patients with AKI-D who were dialysis free for .90 days was analyzed for risk of subsequent ESRD (defined as dialysis requirement for at least 90 days).…”
Section: Long-term Outcomes Of Patients With Aki-d Who Become Dialysimentioning
confidence: 99%
See 1 more Smart Citation
“…The authors not only demonstrated that the risk of AKI rose cumulatively with worsening CKD and increased proteinuria but that this risk continued post-AKI with an increased chance of reaching the combined endpoint of ESRF or doubling of the serum creatinine. Harel et al followed survivors of dialysis-dependent AKI who had recovered renal function [17]. They showed that preexisting CKD (HR 3.86; 95% CI 2.99-4.98), hypertension (HR 1.82; 95% CI 1.28-2.58) and a higher Charlson comorbidity index score (HR 1.10; 95% CI 1.05-1.15/per unit) were significantly associated with risk of progression to ESRF.…”
Section: Common Risk Factors/pre-existing Comorbiditiesmentioning
confidence: 99%